Mainstreaming Ecosystem Services and Biodiversity in Peri-Urban Forest Park Creation: Experience From Eastern Europe - Sevianu, Eliana; Maloş, Cristian Valeriu; Arghiuş, Viorel; Brişan, Nicoleta; Bǎdǎrǎu, Alexandru Sabin; Moga, Marius Cǎtǎlin; Muntean, Liviu; Rǎulea, Adrian; Hartel, Tibor (Frontiers in Environmental Science, 2021)
Abstract. The social role of peri-urban forests is diversifying and this implies also that peri-urban forests are re-designed to meet and shape social demands. A key challenge is the integration of the social demands for green spaces with the maintenance of key ecosystem structures and processes as well as the biodiversity of the green spaces. Here we report our experience and insights gathered through the implementation of a project targeting a peri-urban forest development near the city of Cluj-Napoca. One key particularity of the project was that it was designed by the city hall in cooperation with a major NGO and the academic sector joined the project in its second stage, with the aim to mainstream ecosystem services and biodiversity within a well-established design concept. After comprehensively assessing the biodiversity and ecosystem services of the targeted forest we found that the ecosystem supply was strongly related to the tree stand structure and the forestry management from the past decades. The public expressed concerns related to parts of the established development design which included built structures, artificial lights, toilets and paved roads, perceiving that these actions will negatively influence the natural environment. We present the modifications undertaken in the project design after the public consultation and deliberation within the implementation team. An anonymous internal evaluation of the implementation team shows appreciation for the human and professional interactions and the resulting innovation and learning opportunities. To improve inter- and transdisciplinary collaborations, there is a need for a good institutional support and financial reward, transparency, and nevertheless good communication within the team. At the end of the Discussion section we present our insights gathered from this interdisciplinary experience in order to guide further similar projects in Central and Eastern Europe.